Biological age and environmental risk factors for dementia and stroke: Molecular mechanisms - Knobel, Pablo; Litke, Rachel; Mobbs, Charles V. (Frontiers in Aging Neuroscience, 2022)
Since the development of antibiotics and vaccination, as well as major improvements in public hygiene, the main risk factors for morbidity and mortality are age and chronic exposure to environmental factors, both of which can interact with genetic predispositions. As the average age of the population increases, the prevalence and costs of chronic diseases, especially neurological conditions, are rapidly increasing. The deleterious effects of age and environmental risk factors, develop chronically over relatively long periods of time, in contrast to the relatively rapid deleterious effects of infectious diseases or accidents. Of particular interest is the hypothesis that the deleterious effects of environmental factors may be mediated by acceleration of biological age. This hypothesis is supported by evidence that dietary restriction, which universally delays age-related diseases, also ameliorates deleterious effects of environmental factors. Conversely, both age and environmental risk factors are associated with the accumulation of somatic mutations in mitotic cells and epigenetic modifications that are a measure of “biological age”, a better predictor of age-related morbidity and mortality than chronological age. Here we review evidence that environmental risk factors such as smoking and air pollution may also drive neurological conditions, including Alzheimer’s Disease, by the acceleration of biological age, mediated by cumulative and persistent epigenetic effects as well as somatic mutations. Elucidation of such mechanisms could plausibly allow the development of interventions which delay deleterious effects of both aging and environmental risk factors.